2023
DOI: 10.1590/fst.115922
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional prospects of some wild edible medicinal plants of District Harnai Balochistan, Pakistan

Abstract: The aim of this research work was to evaluate the nutritional worth of some wild edible medicinal plants of District Harnai, Balochistan. Five wild edible medicinal plants (WEMPs) viz., Ficus carica L., Morus alba L., M. nigra L., Olea ferruginea Royle and Pistacia khinjuk Stocks were collected from study area. Proximate and mineral composition of leaf and fruit samples were quantified. Proximate composition revealed that leaf samples contained significant amount of dry matter, ash and protein content in O. fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The soil composition determines the composition and quantity of elements present in these plants [46]. The of such essential and vital elements in wild plants has also been detected and reported by other researchers in their studies [47][48][49][50][51]. study showed that these WEPs could potentially supplement crucial nutrients and elements in the food and nutrition of beings.…”
Section: Elemental Analysismentioning
confidence: 76%
“…The soil composition determines the composition and quantity of elements present in these plants [46]. The of such essential and vital elements in wild plants has also been detected and reported by other researchers in their studies [47][48][49][50][51]. study showed that these WEPs could potentially supplement crucial nutrients and elements in the food and nutrition of beings.…”
Section: Elemental Analysismentioning
confidence: 76%